Traumatic and Nontraumatic Facial Nerve Disorder: Evaluation of 16 Cases. Issue 3 (August 2016) - Naderpoor, Masoud; Shakeri, Moslem; Ahmadvand, Ali; Panahi, Farid; Salehpour, Firooz; Jafari, Rozita; Sharifi, Give
Abstract : Background: The facial nerve has the longest intraosseous paths of the cranial nerves. There is controversy regarding the surgical approaches and time of surgery to obtain the best outcome after facial nerve surgery. Different surgical approaches depending on severity and location of injury, hearing status, and surgeon skills have been used in facial nerve disorders. Whenever the continuity of the facial nerve has been disrupted, we should restore its continuity. In some instances, an end-to-end reapproximation can be accomplished, but if any tension occurs at the anastomotic site, interposition nerve grafts confer a better chance of allowing facial movement. Patients: In this cross-sectional study, 16 patients with facial paralysis were evaluated and followed up for at least 12 month and at most 36 month. Patients according to cause of paralysis were divided into 4 groups: traumatic (10 cases), iatrogenic (2 cases), chronic middle ear infection (2 cases), and idiopathic (2 cases). All of them were suffering from complete facial paralysis (grade VI). Surgery was performed on those who demonstrated either >90% fiber degeneration in ENOG within 3 weeks of injury or passing >4 to 6 months since the start of paralysis in the absence of regeneration. Finally, 12 decompression only, 1 decompression and end-to-end anastomosis, and 3 decompression and facial nerve grafting were accomplished. Conclusions: Results were good to satisfactory (I-II/VI) in 12 cases, acceptable (III-IV/VI) in 2 cases, and no recovery was observed in 2 cases.